2005
DOI: 10.1158/1078-0432.ccr-05-0674
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Vascular Strategy for Controlling Experimental Metastatic Spread of Human Small-Cell Lung Cancer Cells with ZD6474 in Natural Killer Cell–Depleted Severe Combined Immunodeficient Mice

Abstract: Background: Small-cell lung cancer is often characterized by rapid growth and metastatic spread. Because tumor growth and metastasis are angiogenesis dependent, there is great interest in therapeutic strategies that aim to inhibit tumor angiogenesis. Methods:The effect of ZD6474, an orally available inhibitor of vascular endothelial growth factor receptor-2 (VEGFR-2) and epidermal growth factor tyrosine kinases, was studied in experimental multiple-organ metastasis models with human small-cell lung cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…The concentrations of E7080 required to inhibit endothelial proliferation was lower, as was the dose needed to show antimetastatic effects (10 vs. 50 mg/kg; refs. 25,37,38). Furthermore, we found that E7080 prolonged survival in mice bearing multiple organ metastases of SBC-5 cells those with pleural effusion caused by PC14PE6 cells, clearly indicating that E7080 is a highly active inhibitor of angiogenesis of lung cancers with nonmutant EGFR.…”
Section: Discussionmentioning
confidence: 67%
“…The concentrations of E7080 required to inhibit endothelial proliferation was lower, as was the dose needed to show antimetastatic effects (10 vs. 50 mg/kg; refs. 25,37,38). Furthermore, we found that E7080 prolonged survival in mice bearing multiple organ metastases of SBC-5 cells those with pleural effusion caused by PC14PE6 cells, clearly indicating that E7080 is a highly active inhibitor of angiogenesis of lung cancers with nonmutant EGFR.…”
Section: Discussionmentioning
confidence: 67%
“…In this model, highly bone metastatic SBC-5 cells produced metastatic colonies predominantly into the liver, lung, and bone (10,18). SBC-5 cells transfected with FST gene developed significantly fewer metastases in the liver and lung compared with the parental cell or vector control clone ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Vandetanib is a tyrosine kinase inhibitor of both VEGFR-2 and EGFR, and preclinical studies have confirmed its anti-tumour effects in a range of cancer types (Wedge et al, 2002;Ciardiello et al, 2004;Taguchi et al, 2004;Williams et al, 2004;Yano et al, 2005). Phase III clinical studies are now underway with vandetanib in non-small-cell lung cancer following promising results in phase I and II studies (Holden et al, 2005;Natale et al, 2006;Tamura et al, 2006;Heymach et al, 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In our model, EGFR inhibition contributed to the anti-metastatic effect of vandetanib. Moreover, angiogenesis is essential for the growth of tumours more than 1 -2 mm in diameter (Fidler and Ellis, 1994;Ellis and Fidler, 1996;Yano et al, 2005), and VEGF is necessary for the formation of metastatic tissues at the primary site (Küsters et al, 2007). It is possible that VEGFR inhibition at the primary site may reduce the hematogenic metastasis in cholangiocarcinoma.…”
Section: Anti-metastatic Effects Of Vandetanib In Vivomentioning
confidence: 99%